Effectiveness of Diversity Integration in Cosmetics Career Curriculum - JU-HSUAN YEH (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
This study investigates the effectiveness of incorporating diverse teaching methods into career development courses for students in beauty-related majors at a vocational college in Taiwan. A quasi-experimental design was employed, involving two third-year classes majoring in cosmetics application and management. The experimental group received diverse teaching strategies, while the control group followed traditional theoretical instruction. A "Career Development Scale" was used to assess students’ baseline knowledge, and pre-tests, mid-course tests, and post-tests were conducted. Quantitative data were analyzed using ANCOVA to compare the impact of the teaching methods on students' self-awareness, career awareness, and career planning skills. Findings suggest that diverse teaching methods, such as mock interviews and varied assessment strategies, significantly improve students' career readiness. The study recommends scheduling career development courses prior to internships, integrating visits and guest lectures, and incorporating digital tools like gaming devices to enhance student engagement and career planning outcomes. These approaches may better prepare students for the evolving demands of the beauty industry.